Formalization of Design Patterns and Their Automatic Identification in PLC Software for Architecture Assessment. Issue 2 (2020) - Neumann, Eva-Maria; Vogel-Heuser, Birgit; Fischer, Juliane; Ocker, Felix; Diehm, Sebastian; Schwarz, Michael
Abstract: Due to current trends in automation technology such as mass customization and an increasing variety of products, control software (SW) in automated Production Systems (aPS) is becoming increasingly complex. Thus, the need for suitable modularization strategies as a prerequisite for planned reuse increases. In classical high-level language programming, frequently recurring problems are often solved through reusable design patterns. In the control SW development of aPS, however, this approach is still not widely spread. Hence, this paper investigates how design patterns can be used for evaluating modularity in the context of control SW architecture by proposing criteria for classifying and formalizing patterns in aPS SW structure. On that basis, a prototypical implementation is proposed to evaluate the concept and to enable an automated pattern identification and interpretation in an industrial context.